"It's not healthy and it's decidedly not masculine": a media analysis of UK newspaper representations of eating disorders in males. Issue 5 (29th May 2015) - MacLean, Alice; Sweeting, Helen; Walker, Laura; Patterson, Chris; Räisänen, Ulla; Hunt, Kate
Abstract : Objectives: Recent qualitative research found young men reporting that an expectation that eating disorders (EDs) mainly affect young women led them, and others, to only recognise their symptoms when their ED had become entrenched. This raises questions about how these stereotypes persist. We therefore explored how EDs in males were represented in articles published in UK newspapers over a 10-year period (7.12.2002–7.12.2012), specifically attending to whether newsprint media represent EDs in males as 'gender appropriate', 'gender anomalous' or 'gender neutral'. Design: A qualitative thematic analysis of UK newspaper articles. Methods: We searched two databases, Newsbank and LexisNexis, for newspaper articles including ED and male terms in the lead/first paragraph. Following de-duplication, 420 articles were scrutinised; 138 met inclusion criteria for detailed textual analysis and were imported into NVivo10. Findings: The number of articles peaked in 2008 when a UK politician announced that he had experienced bulimia nervosa. Analysis of how the articles portrayed male ED-related characterisations and experiences revealed that they conveyed ambiguous messages about EDs in males. Despite apparently aiming to dispel stereotypes that only young women experience EDs and to address stigma surrounding EDs in males, many aspects of the articles, including repetition of phrases such as 'a young woman's illness', serve to reinforce messages that EDs are inherently 'female' and so 'anomalous' for men. Conclusions: Newspaper articles represent men with EDs as atypical of men, as a result of having an ED (and any feminising or demasculinising characteristics associated with this), and as atypical of people with EDs, who are still usually portrayed as teenage girls. Such media representations frame a cultural paradigm in which there is an expectation that men may feel shame about or strive to conceal EDs, potentially contributing to men with EDs delaying help-seeking, gaining late access to treatments and reducing chances of successful outcomes.